2021
DOI: 10.3390/antiox10071028
|View full text |Cite
|
Sign up to set email alerts
|

Role of Photobiomodulation Therapy in Modulating Oxidative Stress in Temporomandibular Disorders. A Systematic Review and Meta-Analysis of Human Randomised Controlled Trials

Abstract: This systematic review and meta-analysis (PROSPERO registration; ref CRD 42020198921) aimed to govern photobiomodulation therapy (PBMT) efficacy in temporomandibular disorder (TMD). PRISMA guidelines and Cochrane Collaboration recommendations were followed. Differences in pain reduction assessment by qualitative measurement with visual analogue scale pain (VAS), pressure threshold (PPT) and maximum mouth opening (MMO) were calculated with 95% confidence intervals and pooled in a random effects model with a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 135 publications
(1,132 reference statements)
2
24
0
Order By: Relevance
“…TMD occurs in all age groups, especially in young adults, and the highest prevalence rate is between 20 and 40 years old [ 4 ]. Muscle pain and articular disc displacement are common in adolescents, while degenerative osteoarthropathy has a high incidence in middle-aged and elderly people [ 5 ]. MRI is regarded as the first choice because of its nonradiation and high soft tissue resolution.…”
Section: Introductionmentioning
confidence: 99%
“…TMD occurs in all age groups, especially in young adults, and the highest prevalence rate is between 20 and 40 years old [ 4 ]. Muscle pain and articular disc displacement are common in adolescents, while degenerative osteoarthropathy has a high incidence in middle-aged and elderly people [ 5 ]. MRI is regarded as the first choice because of its nonradiation and high soft tissue resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Although the action mechanisms underlying the beneficial effect of PBM are not fully understood, the most widely accepted mechanism is that PBM improves mitochondrial function, leading to increased ATP production, inhibiting oxidative stress, and reducing inflammation [ 15 , 80 , 81 ]. Furthermore, recent studies have demonstrated that PBM can modulate the gut microbiota and may be a novel gut microbiota intervention in different animal disease models, including Alzheimer’s disease and osteoporosis [ 17 , 82 , 83 ] and, more recently, in patients with Parkinson’s disease [ 84 , 85 ].…”
Section: Pbm Overviewmentioning
confidence: 99%
“…PBM has been used clinically for more than 50 years and studied in various diseases and conditions, such as muscle [ 5 ], wound healing [ 6 ], pain relief [ 7 ], arthritis [ 8 ], hair loss [ 9 ], orthodontic mini-implant stability [ 10 ], neurodegenerative diseases [ 11 ] and most recently in COVID-19 patients [ 12 ]. PBM has been shown over decades to be a patient-directed, adjunctive, effective, non-invasive, and safe treatment option to mitigate mitochondrial dysfunction [ 13 ], oxidative stress [ 14 , 15 ], inflammatory conditions [ 16 ], and, more recently, gut microbiota dysbiosis [ 17 ], which are all primary contributors to CKD. Notably, several studies have demonstrated a positive effect of PBM in different models of kidney diseases, including acute kidney injury, glomerulonephritis, and metabolic syndrome-related kidney injury [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Temporomandibular disorders (TMDs) are classified as degenerative musculoskeletal disorders that cause structural and functional abnormalities (AHMAD, 2021). They are a set of clinical conditions with signs and symptoms in the masticatory muscles, temporomandibular joint (TMJ) and associated structures and pain on palpation of the masticatory muscles (HANNA, 2021). As it is a multifactorial disease, it requires a complex therapeutic approach, with noninvasive therapies being the first option for most patients (BROCHADO, 2019).…”
Section: Introductionmentioning
confidence: 99%